let c be Complex; :: thesis: for g, h being complex-valued Function holds (g + h) (/) c = (g (/) c) + (h (/) c)
let g, h be complex-valued Function; :: thesis: (g + h) (/) c = (g (/) c) + (h (/) c)
A1: dom ((g + h) (/) c) = dom (g + h) by VALUED_1:def 5;
A2: dom (g + h) = (dom g) /\ (dom h) by VALUED_1:def 1;
( dom (g (/) c) = dom g & dom (h (/) c) = dom h ) by VALUED_1:def 5;
hence A3: dom ((g + h) (/) c) = dom ((g (/) c) + (h (/) c)) by ; :: according to FUNCT_1:def 11 :: thesis: for b1 being object holds
( not b1 in dom ((g + h) (/) c) or ((g + h) (/) c) . b1 = ((g (/) c) + (h (/) c)) . b1 )

let x be object ; :: thesis: ( not x in dom ((g + h) (/) c) or ((g + h) (/) c) . x = ((g (/) c) + (h (/) c)) . x )
assume A4: x in dom ((g + h) (/) c) ; :: thesis: ((g + h) (/) c) . x = ((g (/) c) + (h (/) c)) . x
thus ((g + h) (/) c) . x = ((g + h) . x) * (c ") by VALUED_1:6
.= ((g . x) + (h . x)) * (c ") by
.= ((g . x) * (c ")) + ((h . x) * (c "))
.= ((g (/) c) . x) + ((h . x) * (c ")) by VALUED_1:6
.= ((g (/) c) . x) + ((h (/) c) . x) by VALUED_1:6
.= ((g (/) c) + (h (/) c)) . x by ; :: thesis: verum